Biodiesel synthesis assisted by ultrasonication using engineered thermo-stable Proteus vulgaris lipase. (15th November 2017) - Gupta, Shweta; Scott, Daniel; Ratna Prabha, C.; Ashokkumar, Muthupandian
Highlights: Proteus vulgaris lipase was engineered by disulfide bond introduction. Lipase was physically immobilized and entrapped on hydrophobic PS beads. These biocatalyst were utilized in the production of biodiesel using non-edible oil. Ultrasonication was used to improve the efficiency of lipase catalysed transesterification. With sonication 98% yield was obtained in 30 min. Abstract: Nature has evolved and designed enzymes to perform an exquisite array of tasks, but in the pursuit of biotechnological interests, these enzymes must often be improved, altered, or even completely redesigned. In the present work, production of biodiesel was carried out using Neem oil and methanol catalysed by "engineered" Proteus vulgaris lipase (PVL) . Two major issues have been addressed in this study in order to improve the efficiency of biodiesel synthesis by enzyme catalysis. The thermal stability of PVL was increased by introduction of a disulfide bond in G181 and T238 by mutation to cysteines. The transesterification reaction was carried out using sonication under different ultrasonic experimental conditions using a 20 kHz horn. The results showed that the application of ultrasound, using 20 kHz horn with 1 cm tip diameter, decreased the reaction time from 22–24 h to 30 min at an applied power of 40 W and methanol to oil molar ratio of 5:1. Temperature raised due to sonication had no effect on engineered PVL (PVL C181-238 ) activity. A comparative study of wild type (WT-PVL) and engineered PVL C181-238 for different temperature has been performed and results showed that introduction of a single disulfide in PVL significantly stabilized it, increasing the half-inactivation temperature (IT1/2) from 37 °C for the WT-PVL to 50 °C for the PVL C181-238 engineered one. In biodiesel synthesis also after immobilization on (Polysulfone) PS beads, PVL C181-238 showed better performance compared to WT-PVL.